(untitled) (Research, Society and Development, 2021)
The objective of this work was to take advantage of buttermilk and whey for the development of a pineapple and wine flavored fermented dairy product and to characterize the product in physicochemical, microbiological and sensorial terms. The experiment was carried out through four treatments with the following formulations: T0 (70% UHT skim milk and 30% whey), T1 (70% buttermilk and 30% whey), T2 (60% buttermilk and 40% whey), T3 (50% buttermilk and 50% whey). The average treatment values did not differ among themselves, at a 5% level of significance, regarding pH, acidity, viscosity and color. The protein and fat levels decreased with the increase of the amount of buttermilk in the treatment formulations. There was no significant difference, at a 5% level of significance, in the average acceptance values of the 57 judges for flavor, texture, aroma, color and overall impression, with values above 8.0 (9 point scale) for all attributes. In the purchase intention test, there also were no differences, with averages superior to 5.4 (7 point scale) for all formulations. All formulations had counts of total coliforms and E. Coli within the acceptable range, taking into consideration the legislation for fermented dairy beverages. Regarding the lactic acid bacteria, the counts were superior to 1.3 x 107 CFU g-1 and also in accordance with the legislation. It was concluded that the use of buttermilk in the production of fermented dairy products is technologically feasible.